Online Group Buying: What Is There For The Consumers? - ERDOĞMUŞ, ZEYNEP İREM (ELSEVIER SCIENCE BV, 2011)
Online group buying, which is a system that provides daily discounts for various services and products, is a new form of marketing at the junction of promotion and pricing that had attracted the attention of both practitioners and academia. Getting started initially from the USA context in 2008, the system proved successful; and just in a short time, lots of clone group buying web sites has sprung and spread throughout the world. The main reason for that boom is that the method provides a win-win situation to the shareholders of the systems, the firms and the customers. The purpose of this paper is to analyze the online group buying system in Turkey, where the practice is quite new and needs a thorough understanding for future strategy building. The customers were considered as the population of the sample and in depth interview method was used to shed a light on their motivations, behavior, and perception of the online buying system. The results indicated that customers mostly based their decisions on price advantage and discount amount. However, novelty and extraordinary nature of the offer also counted. The customers, on the other hand, complained about the discriminatory and dishonest behaviour of the service providers. Implications for the campaign holder firms, the intermediaries, and for future research were drafted. (C) 2011 Published by Elsevier Ltd. Selection and/or peer-review under responsibility 7th International Strategic Management Conference
Keywords: online group buying; group purchasing; collective buying